Effects of erbium content on the morphological and photoluminescent properties of sol-gel prepared yttrium oxide film. Issue 2 (1st February 2018) - Wang, Tzyy-Jiann; Hua, Fan-Xiang; Chang, Yu-Hsu; Peng, Guan-Lu; Chou, Mei-Hua; Hung, Wei-Kuen
Abstract: This work presents the effects of erbium content on the morphological, structural, and photoluminescent properties of erbium-doped yttrium oxide film prepared by water-added-free gelation and spin coating. Crack-free annealed films with uniform thickness and good adhesion are obtained by spin-coating the precursor solutions synthesized by the water-added-free reaction at a low gelation rate. The proposed process has the features of no crack formation after high-temperature annealing, high film thickness homogeneity, and compatibility with standard semiconductor processes. The morphological and structural properties of the prepared films are investigated systematically by optical microscopy (OM), scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray diffraction (XRD). The OM and SEM measurements show that the variation in film color and film morphology is related to the erbium content. A decrease in the surface roughness with increasing erbium content is exhibited by the AFM measurement. The XRD results indicate that the preferential crystalline plane gradually varies from (400) to (222) as the erbium content increases. The peak PL wavelengths in the visible (VIS) and near-infrared (NIR) ranges appear at the wavelengths of 561.2 nm and 1536.6 nm when the films are excited by pump lasers at the wavelengths of 532 nm and 970 nm. Yttrium oxide film with an erbium content of 5 mol% has the maximal PL intensity for both VIS and NIR ranges. This optimal erbium content results from a compromise between the increase in the number of active erbium ions and the non-radiative recombination due to the erbium ion-ion interaction.